KARTU LOGMAR 50 CM DALAM PEMERIKSAAN REFRAKSI SUBYEKTIF - Marta Angkawijaya; Bunyamin Rizki Abdilah; Nensi Tarigan; Kadaryati Kahfi (Akademi Refraksi Optisi dan Optometry Gapopin, 2020)
The recently challanges nowadays are do the eye examination without face to face. Condition of disability patients that physiologicly couldn’t bear at sitting position, the changes of customer behaviour and pandemic covid – 19 situation drives needs of - easy, convenient and safe - eye examination indirectly by cyberspace. Subjective Refraction eye examination using LogMAR Chart 50 cm would adress the problem of those challenges. Writer uses descriptive methods by literature and electronic media also, such as, The published one by European Board of Ophtalmologi Subcomittee , “American Academy of Ophtalmology” part. Visual Acuity Chart that elaborate visual acuity charts includes LogMAR chart which is more reliable, hence gives the more acurate visual acuity.